Degradation characteristics of hydroxyapatite coatings on orthopedic TiAlV in simulated physiological media investigated by electrochemical impedance spectroscopy - Souto, R. M. (2003)
This paper concentrates on the degradation characteristics of hydroxyapatite (HA) coatings on orthopaedic Ti-6Al-4V alloy while immersed in Ringer's salt solution, which were investigated by electrochemical impedance spectroscopy. Electrochemical impedance spectroscopy measurements were used to in situ characterize the electrochemical behavior of the passivated alloy covered with HA during aging in Ringer's solution. Comparison of the electrochemical data for the coated material with that for the uncoated metal substrate was also performed. The characteristic feature that describes the electrochemical behavior of the coated material is the coexistence of large areas of the coating itself with pores where the substrate is exposed to the aggressive media. The interpretation of results was thus performed in terms of a two-layer model of the film, in which the precipitation of hydrated oxide or phosphate compounds seals the pores left by the ceramic coating. The blocking effect due to salt precipitation inside the pores produces an enhancement of the resistance values, thus effectively diminishing the metal ion release in the system.